Cognitive Therapy as a Psychoeducational Approach in Supporting the Role of Sailor Mothers in Children's Education - Windah Riskasari; Syarifah Faradina (Universitas Negeri Malang, 2025)
This study analyzes the effectiveness of cognitive therapy in reducing anxiety of sailor's wives and its impact on their involvement in children's education. Anxiety due to separation from husband can hinder the mother's role in supporting the child's learning process at home. Using a quasi-experimental design with pre-test and post-test, this study involved 100 sailor's wives who were divided into experimental and control groups. Cognitive therapy interventions included identification of negative thought patterns, cognitive restructuring, and relaxation techniques for four weeks. The results showed that cognitive therapy significantly reduced anxiety (p < 0.01), with anxiety scores in the experimental group decreasing from severe to mild. This decrease in anxiety increased the mother's role in children's education, such as assisting in learning, building more positive communication, and creating a home environment that is conducive to children's academic and emotional development. In conclusion, cognitive therapy not only helps overcome anxiety of sailor's wives but also strengthens their role in children's education. Therefore, this approach can be integrated into psychological support programs for sailor's families